Eliciting Market Demand for Advanced Breeding Clones of Roots, Tuber and Banana Crops in Uganda, Nigeria and Côte D’Ivoire - Mulwa, C.K.; Okoye, B.; Kanon, A.; Okumu, B.; Nnabue, I.; Koffi, C.; Nakitto, M.; Bello, A.; Iragaba, P.; Mobio, A.; Okello, J.J.; Nwanze, O.; et al. (2025)
Roots, tubers, and bananas (RTBs) play an important role in food security and income generation in Uganda, Nigeria, and Côte d'Ivoire, serving as essential sources of food security, nutrition and wealth creation because of the numerous opportunities within the value chain. Despite their significance, demand for improved varieties of these crops is still very low, due to several barriers including, limited access to quality planting materials, low consumer awareness, among others. While these traditional barriers to improved variety adoption are binding, neglect of end-user preferences, especially for quality traits, in the variety development process is gaining tract as an important constraint to widespread adoption of new improved varieties. This has led to a shift in breeding programs towards demand-led breeding for enhanced acceptability of new varieties for higher adoption. These studies aim to understand the acceptability of advanced clones of RTB crops emanating from demand-led breeding lines, as an indication of their acceptability and potential adoption by end-users, and for feedback to the breeding programs on trait prioritization. The studies employ an experimental auction approach to elicit consumer demand for advanced breeding clones of sweetpotato, cassava and plantain across three countries (Uganda, Nigeria, and Cote D’Ivoire), based on various quality traits The study finds that consumer demand for improved sweetpotato clones in Uganda is significantly influenced by sensory attributes such as taste and appearance, and that urban consumers have higher WTP for clones that are nutritionally enhanced and have better taste, compared to their rural counterparts. Similar patterns are observed in Nigeria and Cote D’Ivoire, where cassava products like gari and fufu, and plantain, respectively, are preferred based on traditional consumption traits. The studies highlight the importance of understanding end-user demand for RTBs products, based on intrinsic preferences, and the need for prioritizing quality traits such as taste, nutrition, and visual appearance, in the development of new improved RTB varieties, for enhanced acceptance, demand, and adoption. Similarly, on the demand side, the studies show that enhancing consumer awareness on hidden traits, such as nutritional benefits, are critical in improving demand for varieties with such traits.